Consensus and Controversies Between Pain and Addiction Experts on the Prevention, Diagnosis, and Management of Prescription Opioid Use Disorder. Issue 1 (January 2020) - Kraus, Mark; Lintzeris, Nicholas; Bhaskar, Arun; Alho, Hannu; Alon, Eli; Bouhassira, Didier; Haro, Gonzalo; D'Agnone, Oscar; Dematteis, Maurice; Kern, Kai-Uwe; Maremmani, Icro; Perrot, Serge; et al.
Abstract : Objectives: Prescription opioid use disorder (POUD) is an established public health crisis in many countries, and current evidence indicates it is a growing problem in Europe. Many specialists play a role, including pain and addiction medicine specialists, in the diagnosis and management of POUD, but neither group can fully address these patients' needs alone. The purpose of this consensus process was to bring together experts from pain and addiction medicine to examine the positions of both specialties. Methods: In all, 13 international pain medicine, addiction medicine, and addiction psychiatry experts convened a meeting to formulate a set of consensus statements on the diagnosis and management of POUD. The statements were further refined by a wider group of 22 European expert clinicians. At a second meeting of all 35 participants, a set of controversy statements was also developed to recognize some of the key areas of divergent opinion. Results/conclusions: There was a high level of agreement between pain and addiction specialists. Key themes that emerged were the need to strengthen interdisciplinary communication, a desire for greater education and training for clinicians in both specialties, and mutual acknowledgment of the importance of multidisciplinary management of POUD. The blurred line between poorly managed pain and POUD was also a subject of much discussion, reflecting the difficulties in defining and diagnosing this complex condition. Abstract : Supplemental Digital Content is available in the text